Predictive Factors Contributing to First-Attempt Failure of Pediatric Nurses Regarding Peripheral Venous Cannulation - Aaraj, Faisal Ibrahim Al; Himli, Anoud Mohammed; Zaila, Fatimah Mohmmed; Gaisi, Laila Hassan; Albar, Narjes Rehan; Anpri, Zohor Ali Hasan; Zakri, Taghridah Mohemmad (Journal of Posthumanism, 2025)
Background: First-attempt peripheral venous cannulation is an important procedure in pediatric practice, but the rates of failure are high, because there are several causes of failure that are linked to nurses, patients and the environment. Failure of a procedure may result in suffering on children and inefficiency of nursing. Aim: The purpose of the study was to determine predictive variables that lead to first attempt failure of peripheral venous cannulation among pediatric nurses, the variables investigated included clinical experience, assistive technology, psychological stress, environmental factors, and gender disparities. Method: The study was a cross-sectional study where 294 pediatric nurses in various hospitals took part. The structured questionnaires were used to collect the data on demographics, clinical experience, frequency of procedures, utilization of assistive devices, workload, and psychological stress (PPSS). The results of cannulation were noted on the first attempt. The use of descriptive statistics, ANOVA, Pearson correlations, regression analysis, and independent t-tests was used to test the relationship between variables. Result: The frequency of cannulation per week (F = 7.463, p = 0.000), the self perceived workload (F = 2.915, p = 0.000), and psychological stress were significant in determining the first attempt failure. Clinical experience had a positive correlation to cannulation success (r = 0.305, p < 0.01). The use of assistive technology demonstrated an insignificant effect, and the female nurses experienced more procedural anxiety and performance pressures. Demographic variables did not play any major role. Conclusion: The success rate of first-attempt cannulation is related to the experience of the procedure, workload, and stress management. It is suggested that structured training and specific interventions, such as stress reduction, facilitated use of technology, etc., could be used to improve pediatric cannulation outcomes.